Analisis Pengukuran Kinerja dengan Pendekatan Balanced Scorecard pada LKP X - Putri, Mita Octavia; Stevanus Gatot Supriyadi (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The object of this research is in LKP X and utilizes the Balanced Scorecard method to measure four aspects such as financial, customer, internal business, learning and growth. This approach aids in long-term planning. Primary data sources include financial reports from 2021 to 2022, questionnaires, and secondary data. Data collection methods encompass distributing questionnaires, documentation, and interviews, while data analysis employs a descriptive approach. The research findings indicate a favorable financial perspective with an ROI value of 9.68%. However, the Profit Margin (PM) perspective falls short with a value of -12.26%, while the operating ratio is deemed satisfactory at 111.8%. Customer satisfaction, from a customer perspective, is highly favorable with an average score of 144.2. The perspective of internal business performance is good with a value of 3.5%. And the performance of learning and growth aspect indicates positive performance with an average value of 22.5. . Abstrak. Studi ini dilakukan di LKP X dengan menggunakan metode Balanced Scorecard untuk mengukur keempat perspektif didalamnya: keuangan, pelanggan, bisnis internal, pembelajaran dan pertumbuhan. Pendekatan ini membantu dalam perencanaan jangka panjang. Sumber data utama mencakup laporan keuangan dari tahun 2021 hingga 2022, kuesioner, serta data sekunder. Metode pengambilan data mencakup dokumentasi, wawancara serta penyebaran kuesioner, sedangkan analisa data menggunakan pendekatan deskriptif. Hasil penelitian menunjukkan perspektif keuangan yang positif dengan nilai ROI sebesar 9,68%. Namun, dari perspektif Profit Margin (PM), masih kurang dengan nilai -12,26%, sementara Operating Ratio dalam kondisi baik dengan nilai 111,8%. Perspektif pelanggan menunjukkan hasil memuaskan dengan nilai rata-rata 144,2. Aspek bisnis internal menunjukkan kinerja yang baik dengan nilai 3,5%. Dan perspektif learning and growth menunjukkan kinerja positif dengan nilai rata-rata sebesar 22,5.